APAKAH FOOD INFLUENCER MEMPENGARUHI MINAT CALON KONSUMEN UNTUK MENGUNJUNGI TEMPAT KULINER? - Aqib Abdulmalik; Amron Amron (Value : Jurnal Manajemen dan Akuntansi, 2023)
Every marketer needs media to carry out campaigns about their products or services, one of which is a culinary business. The development of social media has led to content creators with content namely reviewing food or culinary places and known as food influencers, which are currently used by marketers or business owners to promote their culinary places with the aim that their culinary places are increasingly known and visited. This study aims to examine the effect of source credibility, content quality, and electronic word of mouth (e-WOM) on the image perceived by visitors and the effect of perceived image on visitors' interest in visiting culinary places. Purposive sampling approach was used in sampling. The self-administered method was used in the data collection process and using Google Form media in distributing online questionnaires, which in turn obtained a sample of 150 Instagram users who had seen food influencer content in the city of Semarang. The analysis used in this research is Structural Equation Modeling (SEM). The results of this study indicate that source credibility, content quality, and electronic word of mouth have a positive but not significant effect on perceived image and perceived image has a significant positive effect on visiting intentions. Keywords: Credibility, quality, e-WOM, image, intention